The Role of Universities in Empowering Individuals and Society in Afghanistan - Gul Mazloum Yar, Fayaz; Muzammil, Hameedullah (Journal of World Science, 2024)
Universities are not independent entities separate from society; political and social systems influence them and possess significant abilities to shape various sectors. As decision-making institutions, universities are crucial in creating conditions for nurturing transformative leaders. The institutional foundation of universities aims to address the developmental needs of society. A successful university seeks indigenous solutions to real problems. The primary objective of this research is to examine the role of universities as the highest educational and training institutions in empowering individuals and society. Initially, the study explored the literal and terminological meanings of empowerment. It then highlights the essential functions of universities concerning individual and societal empowerment. This research adopts a qualitative method with a descriptive-analytical approach, examining expert opinions, literature reviews, and previous studies. The thematic analysis revealed that universities in Afghanistan significantly contribute to individual empowerment through education, innovation, and cultural preservation while addressing broader socio-economic challenges and promoting political stability. These findings emphasize the crucial role of universities in Afghanistan’s sustainable development.